ASSESSMENT OF LAND USE CHANGE IN SHIVAPURI NAGARJUN NATIONAL PARK: THE CASE OF SUNDARIJAL VDC, KATHMANDU - Shrestha, Sujata; Joshi, Laxman; Dangol, Mukesh (Ecoprint: An International Journal of Ecology, 2014)
This research aimed to assess land use and its change between 1990, 2000 and 2010 in Sundarijal VDC of Shivapuri Nagarjun National Park (SNNP). Land use change was assessed using Landsat TM data for 1990, 2000 and 2010. The drivers of land use change and its implications on ecosystem services were studied through field study comprising reconnaissance survey, questionnaire survey, key informant interviews and focus group discussions. GIS analysis showed that forest land and bare land area declined by 0.19% and 0.53%, respectively from 1990 to 2010, while agricultural land increased by 0.72%. The local people see the change in water quantity and quality, soil erosion and biodiversity loss as impacts of land use change. The key drivers of land use change include over harvesting of fuel wood for alcohol production, timber extraction and non-conducive government policies. Due to limited livelihood options, people residing inside SNNP boundary are involved in illegal extraction of fuel wood mainly for alcohol production. Respondents stressed that alternative livelihood options are required for minimizing such illegal activities. DOI: http://dx.doi.org/10.3126/eco.v20i0.11441 ECOPRINT An International Journal of Ecology Vol. 20, 2013 Page: 53-59